2018
DOI: 10.1097/md.0000000000013074
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical characteristics and thromboembolic risk of atrial fibrillation patients with and without congestive heart failure. Results from the CRATF study

Abstract: Congestive heart failure (CHF) and atrial fibrillation (AF) frequently coexist and are associated with increased risk of cardiovascular events.To compare baseline characteristics, comorbidities and pharmacotherapy in AF patients with concomitant CHF to those without CHF.The study included 3506 real-life AF patients with (37.1%) and without CHF — participants of the multicentre, retrospective MultiCenter expeRience in AFib patients Treated with OAC (CRAFT) trial (NCT02987062).All patients were treated with non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Left atrial (LA) dilation is also a predictor for the development of atrial fibrillation after cardiac surgery, and for the likelihood of an atrial fibrillation recurrence after a patient's initial presentation . Some studies also showed a positive association between atrial structure parameters and cardiovascular events . Cardiac ventricular structural values are important prognostic parameters for predicting patient outcome and represent an important component for the diagnosis of cardiac disease, risk stratification, and therapeutic decision‐making, and it is of high prognostic value in patients with ischemic and nonischemic cardiomyopathy .…”
mentioning
confidence: 99%
“…Left atrial (LA) dilation is also a predictor for the development of atrial fibrillation after cardiac surgery, and for the likelihood of an atrial fibrillation recurrence after a patient's initial presentation . Some studies also showed a positive association between atrial structure parameters and cardiovascular events . Cardiac ventricular structural values are important prognostic parameters for predicting patient outcome and represent an important component for the diagnosis of cardiac disease, risk stratification, and therapeutic decision‐making, and it is of high prognostic value in patients with ischemic and nonischemic cardiomyopathy .…”
mentioning
confidence: 99%
“…A total of 5316 results were retrieved from the search (939 from PubMed and 4377 from EMBASE). After duplicates removal, and title and abstract screening, 130 full-texts were assessed for eligibility, and 46 studies were included for quantitative synthesis (Table 1 and Supplementary material online, Figure S1), with a total of 4 232 784 AF patients included: 3 studies were secondary analyses of randomized trials, 28,38,62 19 cohorts were based on administrative databases, 19,20,26,27,31,32,35,36,39,41,49,50,53,55,56,60,61,63,64 16 were observational multicentre studies, 21,22,24,25,33,34,37,40,42,[45][46][47][48]52,54,57 and 8 were observational single-centre studies 23,29,30,43,44,51,58,…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies all over the world, both the prevalence and incidence of thromboembolism are high in patients with HCM, especially in patients with atrial fibrillation (AF) 12 , 13 , 15 , 22 , 23 . In Asia, based on the data on patients diagnosed with HCM from the entire Korean population between 2005 and 2015, the prevalence of stroke was approximately 10% 24 .…”
Section: Epidemiologymentioning
confidence: 99%